Petunia dihydroflavonol 4-reductase is only a few amino acids away from producing orange pelargonidin-based anthocyanins - Vainio, Jere; Mattila, Saku; Abdou, Sara M.; Sipari, Nina; Teeri, Teemu H. (Frontiers in Plant Science, 2023)
Anthocyanins are responsible for the color spectrum of both ornamental and natural flowers. However, not all plant species produce all colors. For example, roses are not blue because they do not naturally possess a hydroxylase that opens the pathway for delphinidin and its derivatives. It is more intriguing why some plants do not carry orange or scarlet red flowers with anthocyanins known as pelargonidins, because the precursor for this anthocyanin should be available if anthocyanins are made at all. The key to this is the substrate specificity of dihydroflavonol 4-reductase (DFR), an enzyme located at the branch point between flavonols and anthocyanins. The most common example is petunia, which does not bear orange flowers unless the enzyme is complemented by biotechnology. We changed a few amino acids in the active site of the enzyme and showed that the mutated petunia DFR started to favor dihydrokaempferol, the precursor to orange pelargonidin, in vitro. When transferred to petunia, it produced an orange hue and dramatically more pelargonidin-based anthocyanins in the flowers.